PENGARUH REFORMASI BIROKRASI TERHADAP KUALITAS PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MANADO - AMIR, ANNISA; RARES, JOYCE; DENGO, SALMIN (Sam Ratulangi University, 2019)
Current conditions indicate that the personnel of the apparatus is very far from what should be displayed by the personnel of the current apparatus which shows low professionalism, including KKN practices involving apparatus, inappropriate numbers, services for convoluted communities living in patron patterns, clients, less creative and innovative. According to the theory of Mustopadidjaja (2003), the aim of implementing bureaucratic reform is to improve bureaucratic performance to be more effective and efficient, the creation of bureaucracies that are professional, neutral, transparent, democratic, independent and have integrity and competence in carrying out their duties and responsibilities state servants, good and clean government, free from KKN and improve the quality of services to the community. While the quality of public service is the quality of service for bureaucrats to the community that is able to meet the desires or needs of the customer / community. Sinambela (2006: 6-8). For the sake of the realization of an ideal government, the bureaucracy must be a servant of the community. One of the important tasks of the bureaucracy is to provide excellent service for the community. Therefore good public service is one measure of the success of bureaucratic reform. In this study using quantitative research methods and data collection techniques using questionnaires / questionnaires for primary data collection distributed to all employees totaling 36 while the community amounted to 36 so the total sample is 74 people. The results of the study generally explain that there is an effect of bureaucratic reformation on the quality of public services in the Population and Civil Registration Office of the city of Manado, but the changes have not been significant.Keyword: Bureaucratic reform, Quality of public services